Research on trustworthiness measurement approaches of component based BPRAS - Qiang HAN; Yu-yu YUAN (Tongxin xuebao)
Aiming at the absence of measurement methods about formalization on trustworthiness attributes of business process reengineering oriented application server (BPRAS),a cooperation framework of business process modeling and trustworthiness measurement based on BPRAS was proposed.Extracting the features of characteristics and behaviors of components consisting of the application server,an abstraction view of computing between those components based on the framework was presented through process algebraic approaches.Furthermore,relative concepts about its components computing operators were defined in order to construct algebraic model of its software trustworthiness (ST) to support the measurement of trustworthy BPRAS.Finally,an application case was also given.